EFEKTIVITAS SOLUTION FOCUSED BRIEF THERAPY DALAM MENURUNKAN KECEMASAN IBU ANAK BERKEBUTUHAN KHUSUS - Rigel Prameswari Zein; Adnani Budi Utami (CV. Denasya Smart Publisher, 2026)
Anxiety is one of the psychological problems commonly experienced by mothers who have children with special needs, mainly due to high caregiving demands and continuous emotional pressure. This study aimed to examine the effectiveness of Solution Focused Brief Therapy (SFBT) in reducing anxiety levels in mothers of children with special needs. This study used a quantitative approach with a pre-experimental single-case experimental design. The participant was a mother of a child with special needs selected using purposive sampling. The instrument used to measure anxiety levels was a standardized anxiety scale. Data analysis was conducted by descriptively comparing anxiety scores before and after the intervention. The results showed a decrease in the participant’s anxiety level after receiving the SFBT intervention. These findings indicate that SFBT is effective in helping mothers manage anxiety by focusing on solutions and strengthening personal resources. This study recommends the use of SFBT as an alternative psychological intervention for mothers of children with special needs.